On the development of the legislation of the Republic of Uzbekistan on combating corruption (Zien Journal of Social Sciences and Humanities, 2022)
The article deals with the issues of corruption prevention, transparency and fairness in the civil service. The state policy in the field of prevention of corruption in the civil service is considered. The draft law "On the State Civil Service" is analyzed.